PENDIDIKAN AKHLAK REMAJA DALAM KELUARGA DI DESA MEKARWANGI KECAMATAN CISAUK, TANGERANG - Wiwi Cahya Ningsih; Sinta Bela; Ika (Jurnal Konseling Pendidikan Islam, 2021)
The position of morals in human life occupies a very important place, because whether an individual or a society is bad or bad depends on how good they are. Moral education in the family is carried out with examples and examples from parents. The behavior and manners of people in the social relationship between mother and father, the treatment of parents towards their children, and the treatment of parents towards other people in the family and community circles will be role models for children. So the child's moral education begins with the education provided by both parents, because the child will imitate the behavior of his parents. If the parents exemplify good behavior, then the child will be good, but on the contrary, if the parents do not reflect good morals, how will they provide good moral education to their children. This study aims to describe how the moral education of adolescents in the family in Kandang Village, Mekarwangi Village RT 04 RW 02 Cisauk Tangerang. Through a phenomenological approach with this qualitative type, it tries to examine more deeply the application of adolescent moral education in families in Mekarwangi village. Research results The results showed that parents in Mekarwangi village have been carried out well, it can be seen from the role of parents as the main mentors who have to teach about morals, so that teenagers will get used to good morals, habituation to adolescents, provide examples. firstly to adolescents also advise children to continue to behave in a moral way. The conclusion is that the moral education of adolescents in the family in Mekarwangi Village RT 04/02 has been carried out well, this can be seen from the parents who have applied morals towards the family, especially for their children. And parents provide good teaching and examples to their children.